Mineral composition in some species of grasses along their vegetative cycle - Bittencourt, Aloysio Mario B.; Filgueiras, Maria Regina T.; Castro, Valdemar R. Osorio e; Andrade, Henrique Antonio de S. (Pesquisa Agropecuaria Brasileira, 2014)
The composition of the nutrient elements Ca, Mg, Na, K, Fe, Mn, Cu and Zn in three species of grasses from the coastal zone of the municipality of Niterói (Rio de Janeiro, Brazil) was determined: Elephant, var, Napier (Pennisetum purpureum Schum.), Guinea (Panicum, ,maximum, Jacq.) and Guatemala (Tripsacum laxun Nash,). The samples from each of the species were collected at time intervals of about two months in order to attend their vegetative cycle. Grasses from the Cordeiro region (a high altitude region), "Jaraguá" (Hyparrhenia rufa (Ness.) Stapf.), "Braquiária" (Brachiaria decumbens Stapf. Praim.) and "Gordura" (Mellinis minutiflora P. de Beauv.) were also analysed for those elements but only one sample was collected and, thus, the whole vegetative cycle was not studied. The mineral equilibrium was verified through the variation of the absolute concentration of the elements and by the ratios (K/Na), (K/Mg), and (K/Ca + Mg) + (100/Mn) + (10/Cu). The results suggest that in the researched grasses there was not a perfect equilibrium in the several studied ratios, but very acceptable with the exception of the K/Na ratio.